DAMPAK PERNIKAHAN USIA MUDA (Studi Kasus Di Desa Mattirowalie Kecamatan Libureng Kabupaten Bone) - Akhiruddin, Akhiruddin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
Early marriage is the argreement of man’s or wonen’s physically and spiritually as husband or wife having goal to be family and it based on the God almighty. The study aims to know effect of the early marriage. The kind of the study is qualitative descriptive and to get informant will be done by purposive sampling, data collection technique uses the observation, interview and documentation. Then it is analyzed by reduction data, presentation data and verification data. The results of the study shown that the positive effect are: 1) to avoid free intercourse, 2) To enlighten family’s burden, 3) To learn how to responsible for the family. While the negative effects are 1) Biology (the damage of the woman’s sexual repreduction). 2) Psychology (long lasting trauma), 3) Sociology (unmature waf of thinking so that can damage family harmony), 4) Population (density of population) for couple of childbearing age.